2017
DOI: 10.26656/fr.2017.2(1).109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant capacity of Aidia borneensis leaf infusion, an endemic plant in Brunei Darussalam

Abstract: We investigated the total antioxidant capacity of Aidia borneensis leaf infusion, a Bornean endemic plant, which is traditionally consumed as a home-remedy beverage in Brunei Darussalam. The antioxidant capacity of the infusion of A. borneensis leaves was evaluated by 2,2-diphenyl-1-picryhydrazyl (DPPH) radical-scavenging ability. We found that the infusion shows a relatively high antioxidant capacity, and it was attributed to its high phenolic, flavonoid, and flavanol contents which were evaluated by Folin-Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…This indicates that leaves of the plants in this study, particularly A. borneensis and A. occidentale are potential sources of natural antioxidants. We should note that the total antioxidant capacity of the infusions of the C. asiatica, A. borneensis, and A. occidentale leaves is abruptly increased either with higher brewing temperature or longer brewing time [23]. Similar tendency has also been observed for C. sinensis black and green teas [24].…”
Section: Total Antioxidant Capacitysupporting
confidence: 52%
See 3 more Smart Citations
“…This indicates that leaves of the plants in this study, particularly A. borneensis and A. occidentale are potential sources of natural antioxidants. We should note that the total antioxidant capacity of the infusions of the C. asiatica, A. borneensis, and A. occidentale leaves is abruptly increased either with higher brewing temperature or longer brewing time [23]. Similar tendency has also been observed for C. sinensis black and green teas [24].…”
Section: Total Antioxidant Capacitysupporting
confidence: 52%
“…Similar tendency has also been observed for C. sinensis black and green teas [24]. However, in our previous study, we have demonstrated that more than 90% of the total antioxidant capacity was achieved at brewing temperature of 60°C, for the first 3 min infusion time [23]. The total antioxidant capacity was slowly increased with infusion time [23].…”
Section: Total Antioxidant Capacitymentioning
confidence: 73%
See 2 more Smart Citations
“…To the best of our knowledge, the scientific evaluation of the pharmacological properties of this plant has not been reported yet, except for its antioxidant property. It was found that the leaf infusion of this plant showed a relatively high antioxidant activity, which could be attributed to its high phenolic, flavonoid, and flavanol contents [5].…”
Section: Introductionmentioning
confidence: 97%